2016
DOI: 10.1007/s00296-016-3637-6
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity but not sedentary activity is reduced in primary Sjögren’s syndrome

Abstract: The aim of the study was to evaluate the levels of physical activity in individuals with primary Sjögren’s syndrome (PSS) and its relationship to the clinical features of PSS. To this cross-sectional study, self-reported levels of physical activity from 273 PSS patients were measured using the International Physical Activity Questionnaire-short form (IPAQ-SF) and were compared with healthy controls matched for age, sex and body mass index. Fatigue and other clinical aspects of PSS including disease status, dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 41 publications
3
19
0
Order By: Relevance
“…All the MFI-20 subscales and the fatigue VAS improved from baseline, but with negligible differences between the two treatments. Similar to earlier results using pharmacologic doses, substitution treatment in DHEA-deficient and severely fatigued patients with pSS was not better than placebo (39).…”
Section: Treatment Of Fatigue Pharmacological Treatmentsupporting
confidence: 86%
See 1 more Smart Citation
“…All the MFI-20 subscales and the fatigue VAS improved from baseline, but with negligible differences between the two treatments. Similar to earlier results using pharmacologic doses, substitution treatment in DHEA-deficient and severely fatigued patients with pSS was not better than placebo (39).…”
Section: Treatment Of Fatigue Pharmacological Treatmentsupporting
confidence: 86%
“…Different non-pharmacological interventions for fatigue have been investigated in other rheumatic diseases (53), and selfmanagement training through patient education programs, cognitive-behavioral therapy, and mindfulness could also be tested in pSS. The positive effect of placebo observed in therapeutic clinical studies (38,39) does indeed give promise for cognitive behavioral interventions. Ongoing studies investigating treatment of SS with fatigue as the primary outcomes are listed in Table 2 and include biological agents as well as alternative treatments such as dietary supplements and acupuncture.…”
Section: Discussionmentioning
confidence: 95%
“…According to latest epidemiological data, the prevalence of pSS is about 0.29 to 0.77% in China (Chinese Rheumatology Association, 2010), and the incidence and prevalence rates global wide are 6.92 (95% CI 4.98 to 8.86) per 100,000 persons and 60.82 (95% CI 43.69 to 77.94) per 100,000 persons, respectively (Qin et al, 2015). Key symptoms such as glandular features, musculoskeletal pain, and fatigue can result in harsh physical limitations, immense psychological distress, and severe complications such as lymphoma, even greater financial burdens on patients' family in long term, which has been considerably affecting their quality of life, making it a heated research focus for medical specialists worldwide (Lackner et al, 2017; Ng et al, 2017; Stack et al, 2017; Alunno et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue is known to be associated with lower aerobic capacity16 and lower physical activity levels 17,18. Wouters et al have shown that pSS patients with lower physical activity, higher activity avoidance, and greater somatic focus have more severe symptoms of fatigue 19.…”
Section: Introductionmentioning
confidence: 99%